Selection of OptimumRadiant Barrier System (RBS) Location in Double Skin Ventilated Roofs - Ghanim, Mohannad R.; Ahmed, Sabah T. (Al-Khwarizmi Engineering Journal, 2020)
Double skin ventilated roof is one of the important passive cooling techniques that aims to reduce solar heat gain through roofs by reducing both the conduction and convection heat transfer from the roof to the ceiling of buildings. On the other hand, radiant barrier system (RBS) is very powerful in blocking the radiation heat transfer between the two skins. In this research,the effect of placing a thin layer of aluminium foil at different locations on the thermal insulation performance of a double skin ventilated roof model is investigated experimentally and the optimum location that transmits less heat flux from the lower skinis specified.The model is made of two parallel inclined galvanized steel plates. Galvanized steel has been used in the roof construction of industrial buildings and storehouses in Iraq.The radiant barrierisapplied alternately, on the outer surface of the upper skin, on the inner surface of the upper skin, suspended in the airgap between the skins, and on the inner surface of the lower skin.These casesareconsidered as Model A, Model B, Model C, and Model D, respectively. It is found that the radiant barrier can block up to78% of the heat in Model A, 71% in Model B, 94% in Model C, and 91% in Model D as compared with the Basic Model.Since the radiant barrierin both Model C and Model D blocks almost the same amount of heat, the location of the radiant barrierin Model D is chosen as the optimumradiant barrierlocation because this model is more practical.